ANALISIS KINERJA LEMBAGA AMIL ZAKAT PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) KABUPATEN OGAN ILIR DENGAN METODE INDONESIA MAGNIFICENCE ZAKAT (IMZ) - Rangga Ardani; Abu Kosim; Emylia Yuniartie (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2019)
This study aimed to determine the performance of the BadanAmil Zakat Nasional(BAZNAS) in Oganilir Regency. The method used to measure the performance of BAZNAS in OganIlir Regency is the method of Indonesia Magnificence of Zakat (IMZ) in the Indonesian Zakat Development Report (IZDR) 2011 which includes five components of assessment, namely the performance of sharia compliance with legality and institutions, management performance, financial performance, performance utilization and the performance of social legitimacy. This study took five years of research from 2014 to 2018. The results of this study show that in 2014 to 2016 the performance of BAZNAS in OganIlir Regency had a static performance and experienced a significant increase in 2017 and 2018.